State & Local Public Finance - Fisher Ronald C. (Mason, OH, USA : Thomson South-Western, 2007)
This undergraduate textbook analyzes the economic theory behind the goods and services provided by local and state governments, and applies the concepts to education, transportation, health and welfare, and economic development policies.
Includes Bibliographical References and Index.
Keywords: Finance, Public United States States; Intergovernmental fiscal relations; United States-municipal relations